Tingkat Kepuasan Pengguna Aplikasi Pengolahan Alat Ungkap Masalah (AUM) berbasis Website ditinjau dari gender - Ifdil, Ifdil; Sin, Tjung Hauw; Fadli, Rima Pratiwi (Universitas Negeri Padang, 2021)
Technological advancements have an impact on a variety of disciplines, including education. As a result of these changes, several inventions and technical advancements have been made to increase the quality and quantity of education. The existence of a Website-based General AUM (Problem Expression Tool) for School Counselors is one of these advances. This Web-based AUM training was conducted for school counselors from all around West Sumatra. 41 people were polled about how satisfied they were with the general AUM application. School counselors who work in high school and junior high schools are among the survey's participants. Online surveys are used as a data collection strategy. Data was analyzed using Jeffreys' Amazing Statistics Program (JASP) software, which included an independent sample t-test. Male and female research respondents have the same level of pleasure, according to the data. As a result, this application might be construed as assisting BK teachers/counselors in completing needs assessments or studies in counseling